Allied health professionals cognitive workload scale in Malacca, Malaysia: A psychometric properties evaluation. - Md Rasid, Shahirah; Mohd Rasdi, Hanif Farhan; Cheng, Jin Wen; Mohd Suadi Nata, Dayana Hazwani (Work, 2025)
Background: Cognitive workload has emerged as one of the most important topics that must be understood and addressed because of its impact on errors and work performance that will compromise patient safety. With increasing patient health demands, Allied Health Professionals (AHPs) tend to have heavier cognitive workloads and impact on personal well-being. Objective: Our study aims to determine the validity and reliability of a cognitive workload scale for AHP in Malacca, Malaysia and examine its effect on personal well-being. Method: The instrument comprises items related to human reliability, human-computer interaction, decision-making, skilled performance, training, work stress and cognitive ergonomic effect. The content validation was conducted using the Content Validity Questionnaire with eight expert panels' responses. 120 AHP working in Malacca were recruited using purposive sampling and took part in the study, completing the online questionnaires. To evaluate the validity based on relationships with other measures, the SMEQ scale was also administered. AMOS Version 24 and IBM SPSS Version 26 were used in data analysis. Results: The instrument showed good content validity (CVI > 0.74). After the deletion of six items, the instrument has good convergent validity (AVE > 0.5), discriminant validity (HTMT Ratio < 0.85), composite reliability (CR > 0.7), internal consistency (alpha > 0.7), construct validity the ratio (1.865), CFI (0.900), PCFI (0.821), PNFI (0.738), RMSEA (0.085), IFI (0.90) and test-retest reliability (ICC > 0.6). The study found a positive correlation with the Malay version of SMEQ. This study also found that the AHP in the laboratory group have higher work stress and experiences more cognitive load effects, leading to lower personal well-being. Conclusion: Overall, the final version of a scale measuring the cognitive workload is valid and reliable in assessing cognitive ergonomics among AHP. Testing cognitive workload on different work populations, including manual and non-manual workers, is recommended for future studies.